Systematic analysis of the methodological structure of the lean literature. Issue 4 (24th February 2021) - Francis, Mark; Thomas, Andrew; Fisher, Ron
Abstract : Purpose: The purpose of this paper is to analyse and evaluate the methodological structure of the lean literature, so that its characteristics and influence among academics and practitioners might be better understood. The authors define "methodological structure" to be comprising six categorical components: publication category, degree of methodological disclosure, research strategies and data collection instruments (DCIs), type of data collected and analysed and type of research informants. Design/methodology/approach: This study is a systematic bibliometric analysis of the lean literature. It has a two-stage research design. The first stage involves the identification of the top 50 most highly cited publications on "Lean", with the resultant reference details being entered into a focal population set (FPS) spread sheet. The second stage involves coding and adding the six component fields of the methodological structure for each of the FPS entries. Both citation analysis (CA) and publication counting are then used to analyse patterns in these six components of methodological structure. Findings: The top 50 publications in the FPS represent over 52, 700 citations. All are either journal papers or books, but books are the most influential. Based upon this FPS sample, the lean literature is found to be both largely atheoretical in nature and also methodologically weak. Over half of the FPS publications are viewpoint-type publications and 46% have no methodological disclosure. The lean literature is predominantly qualitative in nature. Where disclosed, the most common research strategy is the case study and the most common DCI is the interview. High- and mid-level managers are the most frequently encountered research informants, while shop floor workers are infrequently used. Originality/value: This paper starts with the most extensive known systematic review of systematic reviews of the lean literature; the result of which is the characterisation of a number of gaps in this body of knowledge. One of these gaps is the lack of any previous CA. The paper then proceeds to address this gap by providing the first CA within the lean literature. This is also the most comprehensive known CA within the field of operations and supply chain management more generally. As a consequence of this analysis, previously unknown patterns and insights into the methodological structure of the lean literature are revealed.